2020
DOI: 10.1186/s40249-020-00665-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of delayed diagnosis and treatment of tuberculosis in Cambodia: a mixed-methods study

Abstract: Background Cambodia is among the 30 countries in the world with the highest burden of tuberculosis (TB), and it is estimated that 40% of people with TB remain undiagnosed. In this study, we aimed to investigate the determinants of delayed diagnosis and treatment of TB in Cambodia. Methods This mixed-method explanatory sequential study was conducted between February and September 2019 in 12 operational districts in Cambodia. It comprised of a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The generalizability of our findings was limited, because not all ODs in Cambodia were included in the sampling frame. However, the sex ratio and the trends in the proportion of bacteriologically confirmed TB by age groups [ 10 ] were comparable to the most recent national TB prevalence survey [ 39 ]. In comparison with the cases notified to the NTP in 2018 [ 40 ], the age and sex distribution of our sample also reflected a similar trend.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The generalizability of our findings was limited, because not all ODs in Cambodia were included in the sampling frame. However, the sex ratio and the trends in the proportion of bacteriologically confirmed TB by age groups [ 10 ] were comparable to the most recent national TB prevalence survey [ 39 ]. In comparison with the cases notified to the NTP in 2018 [ 40 ], the age and sex distribution of our sample also reflected a similar trend.…”
Section: Discussionmentioning
confidence: 67%
“…Missing TB cases or delayed diagnosis is an issue affected by various factors, including stigma. In Cambodia, TB stigma, rural dwellers, seeking private healthcare, and self-medication before TB diagnosis were found to be associated with delayed TB diagnosis [ 10 ]. The effects of stigma, by and large, on health are deleterious.…”
mentioning
confidence: 99%
“…The private sector relatively outperformed the public sector regarding the delivery of care and medicines availability [ 178 ]. The discrepancies in effectiveness and efficiency were highlighted as a facilitator to seek private healthcare, which eventually leads to a delay in TB diagnosis in a high TB burden setting like Cambodia[ 179 ]. Narrowing down to high TB-burden countries, the quality of public and private healthcare was also found to be below par, and systematic evaluations are needed to identify gaps in the TB care pathway [ 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among LIC and LMIC, a systematic review reported that the quality of health care in public and private sectors was poor, of which the private sectors relatively outperformed the public sector with regards to the delivery of care and medicines availability [175]. The discrepancies in effectiveness and efficiency were highlighted as a facilitator to seek private healthcare, which eventually leads to a delay in TB diagnosis in a high TB burden setting like Cambodia [176]. Narrowing down to high TB-burden countries, quality of both public and private healthcare were also found to be below par, and systematic evaluations are needed to identify gaps in the TB care pathway [157].…”
Section: Health System and Treatment Delaymentioning
confidence: 99%